Benthic and substrate cover data derived from field photo-transect surveys for the Townsville to Whitsunday management region of the Great Barrier Reef (GBR), May/June 2019 - Roelfsema, Christiaan M; Kovacs, Eva M; Markey, Katherine; Phinn, Stuart R (PANGAEA, 2022)
A subset of photoquadrats were uploaded to the CoralNet machine learning interface (https://coralnet.ucsd.edu/) and manually labelled for coral, algae or substrate type using 50 points per quadrat. Follow training of the machine, this training set enabled automatic annotation of all unclassified field images: the remaining field photos were uploaded to the database and 50 annotation points were overlaid on each of the images. Every point was assigned a benthic cover category from a label list automatically by the program. The resulting benthic cover data of each photo was linked to GPS coordinates, saved as an ArcMap point shapefile, and projected to Universal Transverse Mercator WGS-84.